PENALARAN HUKUM DAN KONSEP HUKUM H.L.A. HART SEBAGAI SOLUSI UNTUK MEREDAKAN GEJALA ANTINOMI DALAM PENEGAKAN HUKUM DI INDONESIA - I Wayan Budha Yasa (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2023)
Antinomy is a symptom that is difficult to avoid within the scope of the law. Antinomic symptoms can occur in laws and regulations as well as in law enforcement carried out by judges. To relieve antinomic symptoms, a study of the symptoms of the antinomy and solutions is needed. The preparation of this article aims to examine and describe the intermediate antinomic symptoms in law enforcement in Indonesia between expediency, legal certainty, and justice. In addition, the author will also examine the legal reasoning and the concept of law H.L.A. Hart as a solution to relieve the symptoms of the antinomy. Normative research methods are used for the purposes of compiling this article by prioritizing a conceptual approach to analyze the legal material used. The legal material collected as a support for writing this article is qualitatively constructed and presented descriptively. The results of the study show the antinomic symptoms between legal certainty, justice, and expediency are difficult to avoid in law enforcement in Indonesia. One example of the antinomic symptoms is in law enforcement carried out by judges on cases of illegal fishing in the Indonesia EEZ area. To relieve these antinomic symptoms, legal reasoning and the concept of law H.L.A. Hart can certainly be a solution, but good legal reasoning is needed by the judge in his consideration of deciding the case, while for the concept of law H.L.A. Hart must be clear about the existence in the Indonesian legal system.